2010
DOI: 10.1002/ceat.200900489
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Absorption into Aqueous Solutions of a Polyamine (PZEA), a Sterically Hindered Amine (AMP), and their Blends

Abstract: Among numerous techniques existing for reducing CO 2 emissions, CO 2 capture by absorption in aqueous alkanolamine solutions was specifically studied in this work. For the choice of the adequate amine solution, two major criteria must be taken into account: absorption performances (higher with primary and secondary amines) and energy costs for solvent regeneration (more interesting with tertiary and sterically hindered amines). The different types of amines can also be mixed in order to combine the specific ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 24 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…The effect of different amine concentrations on the CO 2 capturing efficiency was studied in [8,34], and it was confirmed that the efficiency increases with increasing amine concentration. However, industrial amine-treating systems, which are based on the application of MEA and DEA solutions, usually operate within the concentration range from 15 to 30 wt % [35][36][37].…”
Section: Comparison Of Activated Mdea Absorbent Withmentioning
confidence: 73%
“…The effect of different amine concentrations on the CO 2 capturing efficiency was studied in [8,34], and it was confirmed that the efficiency increases with increasing amine concentration. However, industrial amine-treating systems, which are based on the application of MEA and DEA solutions, usually operate within the concentration range from 15 to 30 wt % [35][36][37].…”
Section: Comparison Of Activated Mdea Absorbent Withmentioning
confidence: 73%
“…3.1.5 Addition of piperazine. Utilization of systems based on the sterically hindered amines 16,17 and concentrated, aqueous piperazine (PZ) has been recently reported for CO 2 capture. 18 Piperazine acts as an activator in CO 2 absorption and plays a significant role in the improvement of mass transfer in any scrubbing process.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…15 Aqueous PZ solutions have been investigated as absorbents per se and as an activator in amine solutions. [16][17][18][19] As potential ''green'' solvents, ionic liquids are currently under intensive research. Due to their unique properties, in particular frequently demonstrated negligible vapour pressure and high thermal stability, they have attracted a lot of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Another activator, (piperazinyl-1)-2-ethylamine (PZEA) was investigated by Dubois et al 62 Pure PZEA and AMP as well as a mixture of the two with other amines are investigated to compare the performances for CO 2 absorption. The positive effect of the addition of PZEA in MEA, MDEA and AMP were clearly shown through the experiments, while the addition of AMP into MEA also showed interesting activation results.…”
Section: Addition Of Additivesmentioning
confidence: 99%